The Ottoman Period in Damascus (18th Century). The al-Sibāʻī Mansion: Surviving Evidence of a House with Three Courtyards - Fayyad , Imane (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
Recently restored, the al-Sibāʻī mansion (n.227 in the Ma’ḏanat al-Šaḥim district) is located in the al-Daqqāqīn district, not far from Bāb al-Ḥadīd, very close to the sūq Midḥat Bāšā and the sūq al-Bzūriyya. It is built in a commercial area within Old Damascus, on al-Daqqāqīn Street, in the extension of the sūq Bzuriyya, one of Damascus’ largest souks. It is a vast mansion, ordered around three courtyards, which shed light on the form of dwellings during the last Ottoman period in Damascus (18th-19th century). The aim of this article is to deepen and complete the existing documentation on Syrian heritage and thus safeguard, at least in memory, the originality of this building. Our work will focus on the historical, architectural and decorative analysis of this building.